Effect of Analytical Method on Vitamin C Tablet Levels Stored under Different Temperature Conditions - Susanti, Maria Mita (Media Farmasi Indonesia, 2024)
Vitamin C tablets are commonly consumed by the public as antioxidant supplements. Vitamin C is highly susceptible to oxidation, which is accelerated by factors such as heat, light, alkali, enzymes, oxidizers, and the presence of copper and iron catalysts. Oxidation will be inhibited if vitamin C is left in an acidic state or at low temperatures. However, many vitamin C tablets are not stored according to recommended conditions due to inadequate temperature control during storage or distribution, leading to changes in their vitamin C levels. Vitamin C levels can be analyzed using the Iodimetry method and UV-Vis spectrophotometry. This study aims to determine the effect of the analysis method on the content of vitamin C tablets stored at various temperature variations. This is an experimental research. The independent variable of this study is the analytical method of determining vitamin C content and the dependent variable of this research is the content of vitamin tablets stored at low temperature (2-6°C), room temperature (27-30°C), and high temperature (48°C). Quantitative analysis of vitamin C levels was conducted using both iodimetry and UV-Vis spectrophotometry methods. The highest vitamin C content was found in the analysis of levels using the UV-Vis spectrophotometry method. Statistical analysis shows significant differences, indicating that the method of analyzing the levels of vitamin C tablets stored under varying temperature conditions affects the levels of vitamin C tablets.